Nutritional and biochemical characteristics of oil palm (Elaeis guineensis Jacq.) seedlings in relation to Ganoderma basal stem rot - Fonguimgo, Tengoua Fabien (2014)
Basal stem rot (BSR) of oil palm caused by the fungus Ganoderma boninense is a highly damaging disease in South-east Asia. It is expanding gradually in some oil palm growing countries in Africa and South America. Up to date, available control measures have some limitations. Micronutrients known to have some beneficial effects on disease control have not been assessed on BSR yet. This study investigated the nutritional and biochemical characteristics of six oil palm progenies in relation to BSR. The optimum concentrations of boron (B), copper (Cu) and manganese (Mn) for the growth of oil palm seedlings was determined. Their subsequent effect on nutritional, biochemical and growth parameters of oil palm seedlings was tested prior to evaluating their effects on Ganoderma incidence and severity. The six oil palm progenies reported to respond differently to Ganoderma attack were found effectively different in many parameters. For instance, progenies were significantly different for their root nutrient content except for Zn. With the exception of leaf Cu, progenies also differed significantly in their leaf nutrient content. No significant difference was observed among progenies at 6-7 months for lignin in roots, but by 16-17 months, lignin content in roots of progenies significantly differed. All enzyme activities were significantly different in roots of oil palm progenies at 6-7 months. At 16-17 months, progenies significantly differed only for peroxidase activity. Two (2) mg B/mL and 2 mg Cu/mL of culture solution were identified as optimum concentrations for the growth of oil palm seedlings. All the tested concentrations of Mn (5, 10, 15 and 20 mg/mL) were phytotoxic, but 2 mg Mn/mL was maintained for subsequent studies to maintain nutrient balance. The single and combined concentrations of the selected micronutrients on oil palm seedlings generally increased SPAD chlorophyll value, plant height, and plant biomass compared with the control (no B, no Cu, and no Mn), suggesting the importance of B, Cu and Mn for the growth of oil palm seedlings. Apart from the control, no treatment was consistently higher or lower than the others for the studied parameters. Hence, all the treatments were formulated in forms of fertilizers and tested on Ganoderma incidence and severity. Treatment T9 (B + Cu + Mn) in general gave the poorest performance for most growth and physiological parameters. Double combinations of treatments, T6 (B + Cu), T7 (B + Mn) and T8 (Cu + Mn) generally performed better than other inoculated treatments for nearly all the parameters assessed. In conclusion, a proper nutritional environment may effectively reduce Ganoderma incidence and severity; and the double combination of micronutrients may be more effective than individual nutrients or their triple combination.